The major factors influencing Olympic Bids: A case study of the PyeongChang Winter Olympic Games bids of 2010, 2014 and 2018 - Jung, Jin Hyung (Πανεπιστήμιο Πελοποννήσου, 2013)
PyeongChang had been a low-profile city of the Republic of Korea until the city was elected to host the 2018 Winter Olympic Games after experiencing two-time failures of its bid for the 2010 and 2014 Olympics. Taking the PyeongChang’s three-time bids for the 2010, 2014 and 2018 Winter Olympic Games as case studies, this study, thus, will explore the main reasons of the failures and success of bids of PyeongChang. Preuss (2000) develops “a Multidimensional Decision” which discusses seven factors influencing the decision of the IOC member’s votes for an Olympic host city. The concept of Sports Diplomacy is also considered as an important factor in the Korean context. In light of Preuss’s model, one of the factors ‘Lobbing and Corruption’ may be replaced with the concept of Sports Diplomacy in the Korean context and, thus, this study applies the concept of Sports Diplomacy to the Preuss model in order to analyze the case of PyeongChang bids for the 2010, 2014 and 2018 Winter Olympic Games. The main reasons of the failures of the 2010 and 2014 PyeongChang bids for the Winter Olympic Games was that the quality of the bid was less qualified than the counterparts with a low international recognition and a weak performance in winter sports games. Also these bid campaigns lacked representative figures who were able to influence IOC members and lead the campaign with unity. In particular, the strong engagement and influence of the political power of Russia and the strong leadership presence of President Putin may have influenced the IOC members’ decisions for the 2014 bid. Moreover, the 2008 Beijing Olympics were hosted just two years before the 2010 Winter Olympics and in the same year of the 2014 bid, Korea was perceived to monopolize the major sports events by hosting 2014 Asian Games as well as 2011 IAAF World Championship. Just like the bid for the 2010 games, the 2014 PyeongChang Bid Committee simply emphasized the promotion of peace on the Korean Peninsula through Olympic Movement. For the successes of the 2018 bid, a more upgraded compact venue plan and improvement of Korean’s performance in winter sports were main elements. The Bid Committee also decided to have a strategic and efficient approach to the IOC members in support of the Korean central government’s active involvement. Fortunately, the 2018 votes seemed to have less intervention in terms of past location. Furthermore, the 2018 Bid Committee created key supporting messages and created a new brand for PyeongChang, the “New Horizons”, with a clear purpose to distance themselves from the two previous losing bids and to carve out a clear and distant difference from Munich and Annecy. New Horizons is about potential and growth and giving people access to winter sports for the first time in their lives – as well as creating a sustainable winter sports hub in Asia.
Keywords: Winter Olympics; Olympic host city selection - PyeongChang; Olympics - Planning; Χειμερινοί Ολυμπιακοί αγώνες; Ολυμπιακή επιλογή πόλης υποδοχής - PyeongChang; Ολυμπιακοί αγώνες - Σχεδιασμός; Bid; A multidimensional decision; Sports diplomacy; Failures and successes of PyeongChang bid for the 2010, 2014 and 2018 Winter Olympic Games; Προσφορά; Μια πολυδιάστατη απόφαση; Αθλητική διπλωματία; Αποτυχίες και επιτυχίες της προσφοράς PyeongChang για τους Χειμερινούς Ολυμπιακούς Αγώνες 2010, 2014 και 2018